Impact of Working Capital Management on Business Performance: Case Study of Listed Companies in the Food and Beverage Industry in Vietnam - et. al., Hoang Duc Le, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the impact of working capital management on firm performance, particular in Food and Beverage Industry in Vietnam from 2012 to 2019. The research mainly used secondary data from financial statements of 30 listed companies in the Industry. The result of this study shows that working capital management plays an important to role on firm performance. Each components of working capital would affect differently in firms’ business performance.